2007
DOI: 10.1592/phco.27.9.1263
|View full text |Cite
|
Sign up to set email alerts
|

Enoxaparin Use in the Neonatal Intensive Care Unit: Experience Over 8 Years

Abstract: Enoxaparin may be effective in the treatment of neonatal thrombosis. An initial dosage of 1.5 mg/kg every 12 hours is likely inadequate to obtain therapeutic antifactor Xa levels rapidly and differs for term and preterm neonates. Therapeutic levels in preterm infants may be more variable, and the pharmacokinetics of this drug in preterm infants requires further evaluation. Future studies in neonates should prospectively evaluate a higher starting dose of enoxaparin to document effectiveness, acceptance, compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0
8

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 35 publications
(67 reference statements)
2
71
0
8
Order By: Relevance
“…Subcutaneous enoxaparin seems to be the most frequently used substance in term and preterm neonates. Data published on the use of enoxaparin in 12 preterm and 4 term infants found no serious adverse events and a resolution of TE in 71% of the patients (Malowany et al 2007).…”
Section: Medicalmentioning
confidence: 85%
“…Subcutaneous enoxaparin seems to be the most frequently used substance in term and preterm neonates. Data published on the use of enoxaparin in 12 preterm and 4 term infants found no serious adverse events and a resolution of TE in 71% of the patients (Malowany et al 2007).…”
Section: Medicalmentioning
confidence: 85%
“…111,124,125 However, clinical trials have not been performed to confi rm the safety and efficacy of this approach, and it is diffi cult to recommend the optimal initial dosing strategy for term and premature neonates at this time.…”
Section: Dosesmentioning
confidence: 99%
“…Only one patient, a 24-week infant, required antibiotic treatment secondary to an infected hematoma. 125 LMWH therapy has been effective in the NICU, and centers have reported either partial or complete resolution of TE events between 59 and 100%. 125,126 The traditional initial treatment dose of enoxaparin is displayed in Table 6.…”
Section: Management Of Thrombosismentioning
confidence: 99%
“…125 LMWH therapy has been effective in the NICU, and centers have reported either partial or complete resolution of TE events between 59 and 100%. 125,126 The traditional initial treatment dose of enoxaparin is displayed in Table 6. A recent review evaluating enoxaparin use in 240 neonates found that the mean maintenance dose of enoxaparin ranged from 1.48 to 2.27 mg kg À1 per 12 h for all infants, but was higher for preterm neonates at 1.9 to 2.27 mg kg À1 per 12 h. 125 Therefore, newer recommendations are displayed in Table 6.…”
Section: Management Of Thrombosismentioning
confidence: 99%
See 1 more Smart Citation